Clinical and socioeconomic pattern of infective dermatoses in pediatric population at a tertiary care center of Northeast India - Sagarika Gogoi; Swapan Majumder; Naba Pallab Chetia; Binita Singha (Asian Journal of Medical Sciences, 2024)
Background: Cutaneous disorders are one of the most important components of any health-care system, especially which including children. Infective dermatoses are the most common skin diseases in children. The pattern of dermatoses in children varies from one country to another and within the same country from one state to another due to various climatic, cultural, and socioeconomic factors. Aims and Objectives: The aims and objectives are to study the clinical and socioeconomic profile of cutaneous infections and infestations among children. Materials and Methods: All children up to 12 years presenting with cutaneous infections and infestations were taken as study participants. A detailed history of the disease, socioeconomic status, and housing condition was taken from the patients as well as from the parents. Local, general, and systemic examinations were carried out on all the children and their examination findings were recorded in a standard pro forma for analysis and interpretation of data. Results: A total number of 1932 were children aged 0–12 years patients attended the Dermatology Outpatient Department during the study period of which 665 (34%) presented with infective dermatoses. 61.20% of patients belonged to school-aged children (5–12 years) 76.7% had a family with 4–6 members. 67.67% were from the rural areas, and 77.4% belonged to the lower class. Scabies was the leading offender (29.92%) among infective dermatoses followed by Impetigo contagiosa (20.45%). Conclusion: There is an increased incidence of cutaneous infections and infestations with increasing age among children. The incidence is associated with housing conditions, family size, socioeconomic strata, and seasonal. Most of these conditions are common and controllable with easy preventive and curative measures.